What do platform workers in Poland want? - Kobroń-Gąsiorowska, Łucja; Kuchciński, Artur (Problem zakresu regulacji ustawowej nietypowych form zarobkowania na przykładzie zatrudnienia zewnętrznego i pracy platformowej, 2025)
Although there is still much debate about the legal protection of digital platform workers, there is a lack of research into the preferences of the workers themselves. This is due to the difficulties of conducting traditional social research in this field, which also favors the codified model of worker protection that we are familiar with. Research shows that the key factors influencing the preferences of each group of workers are consistently low wages, job insecurity, occupational risks, and lack of collective voice in decision-making. In addition, the results suggest that the preferences of platform workers are influenced by broader social inequalities, with clear differences depending on gender and country of birth. Once again, the European Union is trying to regulate the rights of digital platform workers with a directive that is intended to protect the sizable market of platform workers. However, the directive does not answer the key question regarding the preferences of the workers themselves and introduces a presumption of employee status. Polish labor law recognizes two separate categories of „employees” The first group includes people who meet the criteria set out in Article 2 of the Labor Code. The second group includes contractors and beneficiaries to whom Polish legislators have gradually granted certain employee rights. Despite the effects of the COVID-19 pandemic, the number of self-employed and digital platform workers in Poland is steadily increasing, leading to legal fiction around contract work. Platform workers often sign contracts for just three hours a week, while most of their income comes from vehicle rental contracts, which allows them to avoid most public law obligations. The full protection afforded by the Polish Labor Code applies only to traditional employees. In contrast, other workers – particularly those employed on a platform basis – are required to register as self-employed or to enter into contracts of mandate or vehicle rental. Consequently, they are classified either as independent contractors or as a hybrid form of semi-independent employees. On the other hand, a research by Copenhagen Economics shows that 68% of couriers in Poland prefer the model of independent contractors.